Static and dynamic behavior of aggrecan solutions. (2020) - Horkay, Ferenc; Basser, Peter J.; Geissler, Erik
ABSTRACT: Small angle neutron scattering (SANS) and dynamic light scattering (DLS) measurements were made on near physiological solutions of a bottlebrush shape polyelectrolyte, aggrecan. Aggrecan is a biologically important molecule whose complexes with hyaluronic acid (HA) provide the osmotic resistance of cartilage. We have investigated the effect of complexation of aggrecan with HA on the structure and dynamic properties of aggrecan solutions. SANS reveals that the supramolecular structure of aggrecan assemblies is only marginally affected by the HA. DLS indicates that the dynamic response of the aggrecan-HA complex is slower than that of the corresponding aggrecan solution. However, addition of calcium ions slightly increases the relaxation rate of the autocorrelation function of the aggrecan solution.